A smart measurer digital ruler system / Abang Afiq Akmal Abg Jalani - Abg Jalani, Abang Afiq Akmal (2024)
Length in definition is to be said as a distance between two points. Measuring distance and length in real life has always been relied on physical measuring tools such as rulers, measuring tape and ropes. Even in the past before mankind relied on physical tools, distance was measured using parts of the human body. Ideally, a modern and futuristic length measurer would be built to modernize and ease how we measure and calculate distance. Sound wave travels in the air can be reflected to where it came from. As such, ultrasonic sensor is one of the finest instruments that will act as a main component for this project. The main modules used in the proposed system are the Arduino UNO for the microcontroller followed by HCSR04 for its main input. In addition, a DHT22 sensor will also be used for accurate measurement application. The HC-05 Bluetooth module and a smartphone with operating Android 4.4 or higher are needed to transfer and display data using the Bluetooth Serial Terminal application. Lastly, the system main output will be displayed through I2C LCD Display and an RGB LED signal indication.